Children Asylum Seekers Face Challenges in the United States - Morton, Andrew; Young, Wendy A. (Refuge: Canada’s Journal on Refugees, 2002)
This article outlines U.S. policy toward children asylum seekers. It highlights the gaps in U.S. detention and asylum policy which jeopardize the protection of children. It also discusses advances made in recent years, such as issuance of the U.S. “Guidelines for Children’s Asylum Claims” which establish evidentiary, procedural, and legal standards for asylum adjudicators dealing with children’s claims. Finally, it suggests reforms that are necessary to bring the United States into compliance with international law and to ensure that children are provided the refuge they deserve.